Adaptasi Manifest Need Questionnaire (MNQ) dalam Konteks Kerja - Femmy Lekahena; Alimatus Sahrah; . Ahmad (LPPM Universitas Proklamasi 45, 2021)
Identifying high or low of employee’s achievement motivation is very important to an organization. This is due to the organization's goals will be more easily achieved in employees who are more likely to make a harder effort to be able to produce better results, and have a desire for success higher than other employees. The aim of this research is to adapt Manifest Need Questionnaire (MNQ), as a tools to measure employee’s achievement motivation in work setting. Adapting MNQ that made in America is very necessary, because instrument to measure employee’s achievement motivation in work settings in Indonesia is still rare. In this research, adapting MNQ is done through three steps, that is initial translation, checking, and back translation. With that adaptation process, MNQ has been adapted into Indonesian culture. It means that MNQ in English version has been translated and adjusted its meaning and context with Indonesian language and culture.